Rancang Bangun Virtual Laboratory Pemuaian untuk SMP - Novi Nurhayati; Ijang Rohman (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2015)
AbstractThis paper describes the development of Virtual Laboratory for simulation lab expansion (VLExpansion) at Junior High School (SMP). The reason of building VL- Expansion is the demands science teaching in the schools which are able to construct mastery of concepts and critical thinking skills within an effective and an efficient. Based on the preliminary studies in several junior high school in Bandung found that: 1) the number of tools to support theexpansion practicum available in laboratories is still limited, 2) practical implementation of such material is infrequency performed, while the practical implementation can build mastery of concepts and critical thinking skills. On the other hand, schools (SMP) have a lots of the computer lab facilities. Nevertheless, in fact it was never done for the science lab. The development steps were conducted, there were: 1) analysis of the concept and indicators ofcritical thinking skills, 2) analysis of the working principle Muschenbroek, 3) extracting the fundamental concepts and phenomena of expansion for various metals, 4) design prototypes VL- Expansion. Thus, the results of the test to the teachers revealed that the VL-Expansion is feasible to be used to construct mastery of concepts and critical thinking skills junior high school students.Keywords: design, virtual laboratory, expansionAbstrakMakalah ini memaparkan pengembangan Virtual Laboratory untuk simulasi praktikum pemuaian (VL-Pemuaian) di Sekolah Menengah Pertama (SMP). VL-Pemuaian dibangun karena kebutuhan dalam pembelajaran IPA di sekolah yang mampu membangun penguasaan konsep dan kemampuan berpikir kritis yang efektif dan efisien. Berdasarkan studi pendahuluan di beberapa SMP di kota Bandung diperoleh bahwa: 1) jumlah alat untuk mendukung praktikum pemuaian yang tersedia di laboratorium masih terbatas, 2) pelaksanaan praktikum untuk materi tersebut jarang dilakukan, sedangkan pelaksanaan praktikum dapat membangun penguasaan konsep dan kemampuan berpikir kritis. Di sisi lain, sekolah-sekolah (SMP) sudah banyak yang memiliki fasilitas laboratorium komputer. Namun kenyataannya tidak pernah dilakukan untuk praktikum IPA. Langkah pengembangan yang dilakukan meliputi: 1) analisis konsep dan indikator keterampilan berpikir kritis, 2) analisis prinsip kerja Muschenbroek, 3) penggalian konsep dasar dan fenomena pemuaian untuk berbagai logam, 4) rancang bangun prototipe VL-Pemuaian. Dari hasil uji coba pada guru diperolah hasil bahwa VL-Pemuaian ini layak untuk digunakan untuk membangun penguasaan konsep dan kemampuan berpikir kritis siswa SMP.Kata-kata kunci: rancang bangun, virtual laboratory, pemuaian